Acute Ethanol Exposure Enhances Synaptic Plasticity in the Dorsal Striatum in Adult Male and Female Rats - Avchalumov, Yosef (Brain Plast, 2020)
BACKGROUND: Acute (ex vivo) and chronic (in vivo) alcohol exposure induces neuroplastic changes in the dorsal striatum, a critical region implicated in instrumental learning. OBJECTIVE: Sex differences are evident in alcohol reward and reinforcement, with female rats consuming higher amount of alcohol in operant paradigms compared to male rats. However, sex differences in the neuroplastic changes produced by acute alcohol in the dorsal striatum have been unexplored. METHODS: Using electrophysiological recordings from dorsal striatal slices obtained from adult male and female rats, we investigated the effects of ex vivo ethanol exposure on synaptic transmission and synaptic plasticity. Ethanol (44 mM) enhanced basal synaptic transmission in both sexes. Ethanol also enhanced long-term potentiation in both sexes. Other measures of synaptic plasticity including paired-pulse ratio were unaltered by ethanol in both sexes. RESULTS: The results suggest that alterations in synaptic plasticity induced by acute ethanol, at a concentration associated with intoxication, could play an important role in alcohol-induced experience-dependent modification of corticostriatal circuits underlying the learning of goal-directed instrumental actions and formation of habits mediating alcohol seeking and taking. CONCLUSIONS: Taken together, understanding the mechanism(s) underlying alcohol induced changes in corticostriatal function may lead to the development of more effective therapeutic agents to reduce habitual drinking and seeking associated with alcohol use disorders.